Application of the Neurofunctional Psychomotor Test for Groups of Children ages 3-14 in Cuenca, Ecuador: A Statistical Analysis of Group Correlations - Huiracocha-Tutivén, Karina; Cappeletti, Piercosimo Tripaldi; Arias, Elida Margarita Proaño; Córdova, Norma Reyes-Fernández de; Salazar, Mery Alexandra Calderón; Simonetta, Elena (Journal of Posthumanism, 2025)
This study was designed to determine if the Neurofunctional Psychomotor Test developed by Elena Simonetta for children and young people from 3 to 14 years old is applicable to the local and regional context of the city of Cuenca, Ecuador. A sample of 793 children and young people was obtained from a universe of 70,838 students through cluster sampling. Fifteen parishes were sampled and the optimal Neyman proportional stratified sampling was applied. The Neurofunctional Psychomotor Test was administered to all 793 students. The results obtained using the uniform rectangular distribution method showed that 75% of the children passed the test. A statistical correlation method was used to determine the linear association between continuous variables. Significant correlations were determined within 95% confidence limits in: correct laterality and temporal perceptions; general dynamic coordination with the postural adjustment variable and tonic control. These significant correlations allowed us to confirm that the Neurofunctional Psychomotor Test was valid when applied to children ages 3-14 in Cuenca, Ecuador. In addition, correlations between pairs of variables were studied for each age group, and cluster analysis methods were applied to investigate global similarities among the variables under study for each age group.